Penguatan Watak Kewarganegaraan Santri di Pondok Pesantren Al-Munawwir Komplek R Krapyak Yogyakarta - Abdinigrum, Aulia Rizki; Supriyadi, Supriyadi (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2023)
AbstractIslamic boarding schools are pedagogical institutions that have strong historical value. In the historical track record of the archipelago, the role of pesantren in maintaining and fighting for the value of love for the homeland is very important. Likewise, at the Al-Munawwir Islamic Boarding School, Complex R, pesantren as an educational institution is highly expected to play a role in growing and studying and implementing civic disposition. The purpose of this study is to the methods and factors that influence, as well as the forms of strengthening the civic disposition in a private and public character. Types of qualitative research. Data collection techniques were carried out with observational studies, documentation, and interviews. The results obtained are an important role in strengthening the civic disposition of students through the methods used, namely the lecture method, advice method, habituation method and exemplary method. Then the influencing factors are internal factors (oneself and habit) and external factors (family, community, ustaz, education and environment). Forms of strengthening private and public character are given in Islamic boarding schools by caregivers, the community and ustaz/ustazah.————AbstrakPondok pesantren merupakan lembaga pedagogik yang memiliki nilai historis kuat. Dalam rekam jejak sejarah nusantara, peran pesantren dalam memelihara dan memperjuangkan nilai cinta tanah air sangat penting. Begitu juga di Pondok Pesantren Al-Munawwir Komplek R, pesantren sebagai lembaga pendidikan sangat diharapkan perannya dalam menumbuhkan dan mempelajari serta menerapkan civic disposition. Tujuan penelitian ini mengenai metode dan faktor-faktor yang mempengaruhi, serta bentuk-bentuk penguatan watak kewarganegaraan pada karakter privat dan publik. Jenis penelitian kualitatif. Teknik pengumpulan data dilakukan dengan studi observasi, dokumentasi, dan wawancara. Hasil yang diperoleh adalah peranan penting dalam penguatan watak kewarganegaraan santri melalui metode yang digunakan yakni metode ceramah, metode nasehat, metode pembiasaan dan metode keteladanan. Kemudian faktor yang mempengaruhi yakni faktor internal (diri sendiri dan habit) dan faktor eksternal (keluarga, masyayikh, ustaz, pendidikan dan lingkungan). Bentuk-bentuk penguatan karakter privat dan publik diberikan di pondok pesantren oleh pengasuh, masyayikh dan ustaz/ustazah.